2019
DOI: 10.4103/joacp.joacp_372_17
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane (TAP) block with levobupivacaine versus levobupivacaine with dexmedetomidine for postoperative analgesia following cesarean delivery

Abstract: Background and Aims: Transverse abdominus plane (TAP) block provides good quality analgesia with minimal side effects. Addition of adjuvant like dexmedetomidine to the local anesthetics has been shown to prolong the action of the block in earlier studies. In this prospective randomised study TAP block with levobupivacane with or without dexmedetomidine was compared with control group for post-operative analgesia following cesarean delivery. Material and Methods: Ninety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
2
4
0
Order By: Relevance
“…According to the results of a previous study [ 14 ] and our pre-experimental observations in six patients, we considered a clinically important reduction of the first request time for PCA to be 3 h. The study sample size was estimated at 28 patients in each group, which was calculated with an α-value of 5 and 80% power. Taking into account the potential for dropouts, 90 patients were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…According to the results of a previous study [ 14 ] and our pre-experimental observations in six patients, we considered a clinically important reduction of the first request time for PCA to be 3 h. The study sample size was estimated at 28 patients in each group, which was calculated with an α-value of 5 and 80% power. Taking into account the potential for dropouts, 90 patients were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, other authors also found prolonged TFA when dexamethasone and dexmedetomidine were used as an adjuvant to LA in their studies [18,20,21]. However, Varshney et al [13] and Parameswari et al [14] reported prolonged TFA (10 h and 14 h respectively) in parturients receiving dexmedetomidine as an adjuvant in TAP block than the present study (7.49±1.02 h). Gupta et al [15] also reported delayed TFA in parturients receiving dexmedetomidine as an adjuvant (19 h).…”
Section: Discussionsupporting
confidence: 58%
“…It acts locally on nociceptive C-fibers to increase the activity of inhibitory potassium channels [12]. The analgesic efficacy of dexmedetomidine and dexamethasone in different doses with different local anesthetics has been evaluated in various studies [13][14][15][16]. In the present study, all patients in three groups were comfortable (VAS<4) till 4 h postoperatively which may be due to the additive effect of SAB to TAP block.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This result was consistent with Joseph et al 85 He discovered that 20 mL of 0.5% ropivacaine combined with 25 µg fentanyl or 25 µg dexmedetomidine effectively prolonged analgesia and reduced total analgesic consumption. Varshney et al 86 and others have also proved this point of view.…”
Section: Application Of Dexmedetomidine In Peripheral Nerve Blockmentioning
confidence: 71%